2022
DOI: 10.3389/fpsyt.2022.1016439
|View full text |Cite
|
Sign up to set email alerts
|

A survey of drug liking and cravings in patients using sublingual or intranasal ketamine for treatment resistant depression: A preliminary evaluation of real world addictive potential

Abstract: Ketamine has gained rapid popularity as a treatment option for treatment resistant depression (TRD). Though seen only in limited contexts, ketamine is a potential drug of abuse, addiction and diversion. Clinical ketamine studies to date have not systematically evaluated factors relevant to addiction risk in patients with TRD, but in treating patients with ketamine, risks of potential harms related to addiction must be considered. As clinical access to intravenous ketamine programs is limited in much of Canada,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…( 93 ) developed a visual analog scale for assessing esketamine craving and drug likeability, intended as a predictor of potential addition ( 94 ). The risk of esketamine addiction does not affect all patients equally ( 95 ). Moreover, slow de-tritation of esketamine and combined use of bupropion were suggested for managing drug-seeking and craving behaviors ( 34 ).…”
Section: Results From the Narrative Clinical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…( 93 ) developed a visual analog scale for assessing esketamine craving and drug likeability, intended as a predictor of potential addition ( 94 ). The risk of esketamine addiction does not affect all patients equally ( 95 ). Moreover, slow de-tritation of esketamine and combined use of bupropion were suggested for managing drug-seeking and craving behaviors ( 34 ).…”
Section: Results From the Narrative Clinical Reviewmentioning
confidence: 99%
“…Although a causal role of dissociation in improving depressive symptoms could be hypothesized, Ballard and Zarate ( 87 ) showed that it is not necessary to determine antidepressant effects of ketamine and derived medication. Moreover, the potential addiction from this drug resulted to involve patients treated with esketamine ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ketamine abuse has been linked to structural alterations in the brain, including reductions in gray matter volume and disruptions in neural connectivity [ 17 ]. Studies have reported significant brain atrophy and neurological dysfunction in individuals with a history of prolonged ketamine misuse, highlighting the need for caution and vigilance in its use [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug-liking, was variable, with a number of patients indicating a dislike for the dissociative effects of ketamine. Overall risk level appeared low, but not negligible ( 81 ). Similarly, there is only one case report of drug seeking behavior and craving in a single patient treated with esketamine ( 82 ).…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…A recent chart review of a sample of patients from our program found SL ketamine was generally started at 50-200 mg, though the most common starting doses were 100 mg and 150 mg. Subsequent increases went as high as 300 mg ( 81 ). IN ketamine was typically started at 100 mg and increased as high as 150 mg.…”
Section: Clinical Considerationsmentioning
confidence: 99%